2017
DOI: 10.15288/jsad.2017.78.531
|View full text |Cite
|
Sign up to set email alerts
|

Gene-by-Environment Interactions on Alcohol Use Among Asian American College Freshmen

Abstract: Among northeast Asians, the variant aldehyde dehydrogenase allele, ALDH2*2 (rs671, A/G, minor/major), has been inversely associated with alcohol dependence. The strength of the associations between ALDH2*2 and drinking behaviors depends on the developmental stage, the phenotype studied, and other moderating variables. This study examined ALDH2 gene status as a moderator of the associations between parental drinking, peer drinking, and acculturation with alcohol use among 222 Chinese American and Korean America… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…There was no evidence for significant interactions of these effects with adoptee genotype. This is generally consistent with prior work finding that close peer alcohol use is associated with alcohol use in those with and without ALDH2*2 (Luk et al, 2017;O'Shea et al, 2017) though we do not find evidence that the associations differ in magnitude by ALDH2 status as has been identified elsewhere (O'Shea et al, 2017). Our results are generally inconsistent, however, with the existing literature finding evidence for parental and sibling effects in both adoptive and nonadoptive families (Irons et al, 2007(Irons et al, , 2012McGue et al, 2014;Samek et al, 2018;Saunders et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…There was no evidence for significant interactions of these effects with adoptee genotype. This is generally consistent with prior work finding that close peer alcohol use is associated with alcohol use in those with and without ALDH2*2 (Luk et al, 2017;O'Shea et al, 2017) though we do not find evidence that the associations differ in magnitude by ALDH2 status as has been identified elsewhere (O'Shea et al, 2017). Our results are generally inconsistent, however, with the existing literature finding evidence for parental and sibling effects in both adoptive and nonadoptive families (Irons et al, 2007(Irons et al, , 2012McGue et al, 2014;Samek et al, 2018;Saunders et al, 2016).…”
Section: Discussionsupporting
confidence: 82%
“…Environmental influences within families and amongst peers may also moderate the protective effects of ALDH2*2 and ADH1B*2. Previous research has found that parent, sibling, and peer alcohol consumption patterns predict continued use in those with the ALDH2 deficiency (Irons et al, 2007(Irons et al, , 2012Luk et al, 2017;O'Shea et al, 2017).…”
mentioning
confidence: 97%
“…This explanation highlights the need for longitudinal research that models changes in alcohol use and tracks possible progression into problematic use over time. This finding also points to the importance of considering multiple sources of contextual influences (e.g., parental, peer, and cultural) and testing gene‐by‐acculturation interactions on alcohol use among racial and ethnic minority students (Luk et al., ). In light of increased evidence supporting Asian ethnic subgroup differences in drinking behaviors (Kane et al., ), it would also be important to consider if the observed increase in alcohol use was driven by particular Asian subgroups such as Filipino, Korean, or Japanese college students.…”
mentioning
confidence: 90%